The Impact of Handbooks on the Concept Understanding and Learning Interests of Students on the Concept of Reaction Rate - Zulham Handayani; A. Halim; Ibnu Khaldun (Postgraduate, University of Mataram, 2021)
This study aims to determine the impact of pocket books on conceptual understanding and student interest in learning. The research method used is quasi experimental using the nonequivalent control group design. The population in this study were students of class XI MIPA SMA Negeri 1 Jaya. The number of samples consisted of 60 people, each class consisting of 30 students. The research instruments used were test questions and questionnaires. The data analysis technique used the conceptual understanding through the N-Gain test and the independent sample t-test, while the interest in learning used the percentage formula. The results of the N-gain test for understanding the concept obtained that the average experimental class was higher than the control class, each class belonging to the criteria for moderate improvement. The results of the independent sample t-test showed that there was a significant difference between the students' conceptual understanding of the experimental class and the control class. The results of interest in learning from each subscale: family support, teacher influence, and learning experience in class in the experimental class obtained a very high category. Meanwhile, on the subscale the attitudes of friends towards chemistry learning and the influence of informal learning were high. For the control class, the category obtained on the family support subscale is high, while the subscale for friends' attitudes towards chemistry learning, teacher influence, informal learning experiences, and classroom learning experiences is in the moderate category. The average percentage of learning interest in the experimental class was obtained in the very high category, while the control class was in the medium category. The conclusion of this study is that the impact of using pocket books on chemistry learning can improve students' understanding of concepts and interest in learning